2009
DOI: 10.1158/0008-5472.can-08-1946
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Microvesicles as Actors in the Establishment of a Favorable Prostatic Tumoral Niche: A Role for Activated Fibroblasts and CX3CL1-CX3CR1 Axis

Abstract: Tumor microenvironment is enriched in plasma membrane microvesicles (MV) shed from all cell types that constitute the tumor mass, reflecting the antigenic profile of the cells they originate from. Fibroblasts and tumor cells mutually communicate within tumor microenvironment. Recent evidences suggest that tumor-derived MVs (TMV) exert a broad array of biological functions in cell-to-cell communication. To elucidate their role in cancer-to-fibroblast cell communication, TMV obtained from two prostate carcinoma … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 38 publications
4
148
0
1
Order By: Relevance
“…In this study, microvesicles released by PC3 cells, an invasive prostate cancer cell line, triggered ERK phosphorylation, MMP9 upregulation, increased motility and resistance to apoptosis in fibroblasts in the surrounding microenvironment. In turn, the activated fibroblasts shed microvesicles to facilitate the migration and invasion of the prostate cancer line (Castellana et al, 2009). A similar feedback phenomenon was reported in yet another study, confirming the role of prostate-tumor-derived microvesicles in the 'activation' of stromal cells in the tumor microenvironment (Di Vizio et al, 2009).…”
Section: Impact On the Tumor Microenvironmentsupporting
confidence: 77%
“…In this study, microvesicles released by PC3 cells, an invasive prostate cancer cell line, triggered ERK phosphorylation, MMP9 upregulation, increased motility and resistance to apoptosis in fibroblasts in the surrounding microenvironment. In turn, the activated fibroblasts shed microvesicles to facilitate the migration and invasion of the prostate cancer line (Castellana et al, 2009). A similar feedback phenomenon was reported in yet another study, confirming the role of prostate-tumor-derived microvesicles in the 'activation' of stromal cells in the tumor microenvironment (Di Vizio et al, 2009).…”
Section: Impact On the Tumor Microenvironmentsupporting
confidence: 77%
“…The supernatant was centrifuged at 4000×g for 1 h to remove the cellular debris, and the resulting supernatant was then distributed into EP tubes for an additional centrifugation at 16 000×g for 1 h. The supernatant was discarded to remove the exosomes, and the MV pellet was washed and resuspended in PBS, followed by another centrifugation at 16 000×g for 1 h to remove the remaining exosomes. The protein content of the MV preparation was quantified using the Bradford method (Bio-Rad, Hercules, CA, USA) as previously reported [24] . All of the centrifugations were performed at 4 °C, and the isolated MVs were stored in PBS at 4 °C until use.…”
Section: Isolation Of Mvsmentioning
confidence: 99%
“…MVs and exosomes are secreted from various cell types (9), and their miRNA content is associated with regulating cellular processes involved in cell communication, angiogenesis, and extracellular matrix remodeling (9)(10)(11). Recently, we revealed that tumor-secreted miRNAs contributed to tumorigenesis by acting in a paracrine manner to signal to target cells.…”
mentioning
confidence: 99%